Dissociation of Endogenous Pain Inhibition Due to Conditioned Pain Modulation and Placebo in Male Athletes Versus Nonathletes - Geisler, Maria; Herbsleb, Marco; Bär, Karl-Jürgen; Weiss, Thomas (Frontiers in Psychology, 2020)
Animals and humans are able to inhibit pain by activating their endogenous pain-inhibition system. Endurance athletes possess a higher pain-tolerance threshold and a greater conditioned pain modulation (CPM) effect than nonathletes, suggesting better endogenous pain inhibition. In addition to CPM, placebo is another prominent paradigm used to test endogenous pain inhibition. However, whether the placebo effect and the CPM effect share the same mechanisms of pain inhibition has not been investigated. If there is a shared mechanism, then endurance athletes should show not only a better CPM effect than nonathletes but also a greater placebo effect. Here, we investigated 16 male endurance athletes and 17 male nonathletes in well-established placebo and CPM paradigms to assess whether endurance athletes have a better endogenous pain-inhibition system than nonathletes. As expected, we find a significantly greater CPM effect in athletes than in nonathletes. In contrast, we could only find a significant placebo effect in nonathletes. Explorative analyses reveal negative associations between the placebo effect and heart rate variability as well as between the placebo effect and interoceptive awareness. Together, the results demonstrate a dissociation of endogenous pain inhibition of CPM and placebo effect between endurance athletes and nonathletes. This suggests that both effects are based, at least in part, on different biological mechanisms.